Reconcilable differences : rebuild your relationship by rediscovering the partner you love--without losing yourself - Christensen, Andrew; Doss, Brian David, 1975-; Jacobson, Neil S., 1949- (New York ; London, UK : The Guilford Press, 2014)
""If only he could see things from my point of view." "Why does she have to act that way?" No matter how much two people love each other, their differences will eventually cause conflict. This popular, science-based guide offers powerful solutions for couples frustrated by continual attempts to make each other change. True acceptance of one another may seem difficult to accomplish, but the clear-cut steps in this book can make it a reality. Aided by thought-provoking exercises and vivid stories, readers learn why they keep having the same fights again and again; how to keep small incompatibilities from causing big problems; what communication strategies really work to resolve conflicts; and how to problem-solve and make positive changes--together. Updated throughout with new research, practical tools, and examples, the second edition features a new chapter on mindfulness"--
Machine generated contents note: I. The Conflicting Sides of Conflict -- 1. Three Sides to Every Story -- 2. "You're Wrong!": Relationship Problems as Faults -- II. A DEEP Understanding of Conflict: The Third Side of the Story -- 3. "How Can You Be That Way?": Relationship Problems as Differences -- 4. "You Know How to Hurt Me": Relationship Problems as Emotional Sensitivities -- 5. "Can't You See I'm Stressed Out?": Relationship Problems as External Circumstances -- 6. A Cure Worse Than the Disease: Relationship Problems as Patterns of Communication -- III. From Argument to Acceptance -- 7. The Delicate Balance: Acceptance and Change -- 8. A Story of Our Own: Acceptance through Understanding -- 9. Walking in Your Partner's Shoes: Acceptance through Compassion -- 10. Getting Some Perspective on the Conflict: Acceptance through Tolerant Distance -- IV. Deliberate Change through Acceptance -- 11. The Dilemmas of Deliberate Change -- 12. Deliberate Change through Mindfulness: Custom-Fitting Change to Suit Your Relationship -- 13. Deliberate Change through Communication: Taking Good Advice about Talking and Listening with a Mindful Grain of Salt -- 14. The Silver Bullet of Deliberate Change: Taking Charge of Change Even When Things Go Bad -- V. When Acceptance Is Not Enough -- 15. "Don't Do That to Me!": Violence, Verbal Abuse, and Infidelity -- 16. Calling In the Professionals: Couple and Individual Therapy -- Resources -- Bibliography.
Includes bibliographical references (p. 333-336) and index.
Keywords: Couples; Man-woman relationships; Interpersonal communication; Interpersonal relations; Conflict management